2022
DOI: 10.1108/cms-09-2021-0381
|View full text |Cite
|
Sign up to set email alerts
|

Cyberloafing at the workplace: effect of Zhong-Yong thinking on mental health and mindfulness as a moderating role

Abstract: Purpose This study aims to integrate conservation of resources theory discus the antecedents and consequences of cyberloafing as well as the boundary effect between cyberloafing and mental health. Design/methodology/approach The authors collected 431 valid questionnaires in four months. Each questionnaire was divided into two parts that had to be distributed. The interval between the first distribution and the second distribution was 15 days. Findings The research study revealed that employees’ Zhong-Yong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“… 14 Although there is a view that China is not a Confucian country, 15 aspects of Confucianism can be found in some Chinese businesses. 16 Zhong Yong thinking (Confucianism) influence on the mental 17 and trait 18 of Chinese employees has been confirmed. The same is true of Taoism, which exists in companies such as Alibaba.com.…”
Section: Introductionmentioning
confidence: 85%
“… 14 Although there is a view that China is not a Confucian country, 15 aspects of Confucianism can be found in some Chinese businesses. 16 Zhong Yong thinking (Confucianism) influence on the mental 17 and trait 18 of Chinese employees has been confirmed. The same is true of Taoism, which exists in companies such as Alibaba.com.…”
Section: Introductionmentioning
confidence: 85%
“…Exhausted employees are more prone to distractions like cyberloafing (Khakpour, 2019;Liu & Zhang, 2022;Maqbool et al, 2023;Rahaei & Salehzadeh, 2020;Lim et al, 2020). This type of distraction is used to avoid interactions with leadership to protect self-esteem and health (Hadadian & Sayadpour, 2018).…”
Section: Emotional Exhaustion As a Mediatormentioning
confidence: 99%
“…In recent years, scholars have recognized that if used appropriately, cyberloafing can have restorative effects [35], and be beneficial for the psychological well-being of employees [36]. Luqman et al found that social media-based interactions with colleagues can help employees alleviate boredom, and promote relaxation [37].…”
Section: Cyberloafing As Restorativementioning
confidence: 99%